Screening of plants with antimicrobial activity against enterobacteria, Pseudomonas spp. and Staphylococcus spp. - Girondi, Camila Miorelli [UNESP]; De Oliveira, Analu Barros [UNESP]; Prado, Jackeline Alves [UNESP]; Koga-Ito, Cristiane Yumi [UNESP]; Borges, Aline Chiodi [UNESP]; Botazzo Delbem, Alberto Carlos [UNESP]; Alves Pereira, Daniel Freitas [UNESP]; Salvador, Marcos José; Brighenti, Fernanda Lourenção [UNESP] (Taylor & Francis, 2017)
Aim: This study screened plants for antibacterial properties against bacteria of medical importance. Materials & methods: 60 extracts were obtained from the leaves of ten plants (Jatropha weddelliana, Attalea phalerata, Buchenavia tomentosa, Croton doctoris, Mouriri elliptica, Mascagnia benthamiana, Senna aculeata, Unonopis guatterioides, Allagoptera leucocalyx and Bactris glaucescens) using different extraction methods: A) Ethanol 70°C/72 h; B) Water/5 min/100°C; C) Water/1 h/55°C; D) Water/72 h; E) Hexane/72 h and F) Ethanol 99°C/72 h. Enterobacteria/Pseudomonas and staphylococci reference strains and 201 clinical isolates were used. Primary screening was done using agar well-diffusion assay. MIC/minimum bactericidal concentration and chemical characterization were determined. Results: Extracts 5F and 3A showed the best MIC/minimum bactericidal concentration against clinical isolates and showed the presence of phenols. Conclusion: The present study demonstrated that Mouriri elliptica and Buchenavia tomentosa were the most active plants against the studied bacteria.
Keywords: biological products; Enterobacteria; Pseudomonas spp.; Staphylococcus